2015
DOI: 10.1136/vr.102977
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of aiming bias in the frontal plane during orthopaedic drilling procedures

Abstract: Drilling trials were performed using drilling boards incorporating pairs of 22 mm polyethylene tubes mounted horizontally. The tubes were premarked with 20, 0.5 mm deep notches along the centre of their upper surface representing the starting point for each drilling trial. Volunteers were instructed to drill 20 straight holes across the tube until they penetrated both walls. Kirschner wires were inserted through each of the drill holes until they made indentations into the base board. Deviation of each mark fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Another recent study assessed the ability of 14 qualified veterinary surgeons to drill holes free hand at 90° from the horizontal ( Sparrow and others 2015 ). They identified a systematic error in all individuals and found that left-handed individuals had a mean aiming bias of 2.3° (range 0–7.7°) to the left and right-handed individuals had a mean aiming bias of 1.5° (range 0.3–3.1°) to the right.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study assessed the ability of 14 qualified veterinary surgeons to drill holes free hand at 90° from the horizontal ( Sparrow and others 2015 ). They identified a systematic error in all individuals and found that left-handed individuals had a mean aiming bias of 2.3° (range 0–7.7°) to the left and right-handed individuals had a mean aiming bias of 1.5° (range 0.3–3.1°) to the right.…”
Section: Introductionmentioning
confidence: 99%
“…Currently established MIO techniques may still result in screw malalignment subsequent to human errors as the surgeon is attempting to manually maintain the initial position and orientation of the drill guide during drilling . Human error while drilling has been identified as a source of inaccuracy in orthopedic surgery and neurosurgery . Although they are not specific to a surgical procedure, drilling inaccuracies may be increasingly relevant in the case of SIL/F repair because of small size and dimensions of the safe sacral implantation corridor .…”
Section: Clinical Relevance—discussionmentioning
confidence: 99%
“…2,3,9 Human error while drilling has been identified as a source of inaccuracy in orthopedic surgery and neurosurgery. 20 Although they are not specific to a surgical procedure, drilling inaccuracies may be increasingly relevant in the case of SIL/F repair because of small size and dimensions of the safe sacral implantation corridor. [15][16][17] Poorly oriented screws may cause iatrogenic damage to the cauda equina dorsally, the lumbosacral intervertebral disc space cranially, or the lumbosacral plexus and median sacral vessels ventrally.…”
Section: Accurate Screw Placementmentioning
confidence: 99%
See 2 more Smart Citations